2021
DOI: 10.1108/jgr-03-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a King? Unveiling the pragmatic micro-perceived value attributes of a fulfilling corporate governance code for responsible sustainable development

Abstract: Purpose A recent contribution entitled Global Responsibility and the King Reports was made to the literature that represents a significant advancement in the understanding of how standards of good governance are practised. The corpus revealed key insights about macro-institutional governance regimes, yet, extraordinarily little about meso-organisational and even less so, micro-individual corporate governance practice. This study aims to shed light on the micro-individual level of corporate governance practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…They shed light on how the King Codes are woven into the social fabric of daily organisational practice. They suggest such knowledge will be of much value to organisations that seek to enhance their CG and social responsibility performance (Thakhathi et al , 2021). In this case, it can be inferred that “knowledge” is an overall value being sought; however, the lack of specificity is problematic.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They shed light on how the King Codes are woven into the social fabric of daily organisational practice. They suggest such knowledge will be of much value to organisations that seek to enhance their CG and social responsibility performance (Thakhathi et al , 2021). In this case, it can be inferred that “knowledge” is an overall value being sought; however, the lack of specificity is problematic.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Interacting with stakeholders and value-seekers is germane to CSR studies. Indeed, of the 23 JGR journals sampled herein, only 2 (Dean et al , 2020; Thakhathi, 2021) do not refer to stakeholders specifically.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The author then analyzed the common quality and timeframe aspects of carbon targets, as well as whether carbon targets differ between carbon-intensive and less carbon-intensive businesses. Further, Thakhathi et al (2021) used qualitative SSIs to shed light on the obscured micro-individual level of corporate governance practice by drawing pragmatic insights from the landmark South African King Code experience that can be applied to other governance jurisdictions for global organizational accountability and responsibility. The combined effect of the literature review revealed that, despite the increase in CE studies, there is still a scarcity of studies that address how accountability manifests within the circularity space.…”
Section: Circular Economymentioning
confidence: 99%